El sagrario renacentista de la iglesia de Santa María de Cistierna: obra de Pierres de la Fuente - Oricheta García, Arantzazu (Estudios humanísticos. Geografía, historia y arte, 1996)
The church of Santa María in Cistierna (León) conserved a renaissance ciborium which was carved by the sculptor Pierres de la Fuente, and that showes a typical yconography in these objetcs based in the imagos of the Calvary and the Cross Descent.